Research on improved cable-length-adaptive sensorless vector control for drives of induction motors in deep-sea oilfields - Jin, Zitao; Deng, Yonghong (Frontiers in energy research, 2025)
IntroductionThis paper addresses the issue of the insufficient adaptability of existing vector control algorithms to filter and compensate for long cable parameters (under the influence of parasitic impedance, parasitic capacitive reactance, and parasitic inductive reactance), which leads to unresolved stability and harmonic issues in long-cable drives for deep-sea oil fields.MethodsBy establishing the complete system transfer function of filter-cable-motor, providing the Lyapunov proof of asymptotic stability, a sensorless vector control algorithm based on Lyapunov theory was proposed. This paper also quantified the analysis of variations in long cable parameters over time in the deep-sea environment and incorporated it into the proposed long cable model. A Lyapunov function was constructed. For further analysis of the stability of the proposed function, the long cable health model was introduced and verified. Simulations were conducted under various frequencies, work situations, and with the introduction of time-sensitivity parameters for long cables. The improved algorithm demonstrates certain adaptability to time-sensitivity parameters and improves the torque and current response of the induction motor.ResultsExperimental verifications on no-load startup, sudden load, and sudden unload were carried out. The Fast Fourier Transform (FFT) simulation results demonstrate that during 10 Hz no-load operation, the Total Harmonic Distortion (THD) decreases from 8.28% to 5.41%; during 30 Hz no-load operation, it decreases from 7.70% to 4.45%; while during 50 Hz no-load operation, it drops from 4.41% to 4.37%. The THD at 10 Hz, 30 Hz, and 50 Hz frequencies drops by 2.87%, 3.35%, and 0.04% respectively.DiscussionFuture work will focus on applications in deep-sea oil extraction and on further improving the simulations and experiments.